PSII-11 Effect of a feed supplement composed of native rumen microorganisms on feedlot steer digestive health. (30th November 2020) - Yang, Fan; Embree, Jordan; Gilmore, Sean; Embree, Mallory M
Abstract: Feedlot cattle that receive high grain diets are prone to developing rumen acidosis. The rumen microbiome is a critical part of feed digestion, and thus naturally occurring, native rumen microorganisms may alleviate digestive distress. A daily, in feed microbial feed supplement (MFS) (Magnius, ASCUS Biosciences Inc, San Diego, CA) containing three native rumen microbes (Chordacoccus ruminofurens, Prevotella albensis, and Succinivibrio dextrinosolvens) was evaluated. Seventy-five commercial feedlot steers (Johnson Research, LLC, Parma, Idaho) were split into three treatment groups, 25 control, 25 low-dose (3E8 cells/steer/day), and 25 high-dose (3E9 cells/steer/day). The study included three periods: acclimation (28 days), grow-out period 1 (68 days), and grow-out period 2 (73 days). The animals were individually penned for the acclimation and grow-out period 1, and were collapsed into 7–9 steers per pen for grow-out period 2. The finishing ration for grow-out period 2 was also adjusted to 89.77% concentrate (DM) from 85.56% during grow-out period 1. No significant performance differences among treatment groups were observed during grow-out period 1. In grow-out period 2, the average daily weight gain of mid-weight steers was significantly higher (P = 0.04) in animals receiving a high-dose of MFS than controls. Additionally, the rumen pH of experimental steers were significantly higher than the controls (P < 0.001) during grow-out period 2. The rumen microbiome shifts further supported the observed pH differences. A strong (R2 >0.6) and significant negative correlation (P < 0.001) was observed between rumen pH and rumen dissolved %CO2 in all three treatment groups throughout the study. This is consistent with literature reporting that rumen CO2 accumulation may contribute significantly to rumen acidosis. These findings demonstrate the promise of using microbial based feed supplements in the improvement of feedlot cattle digestive health and performance.